2009
DOI: 10.1210/en.2008-1647
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Overexpression of Heparin-Binding Epidermal Growth Factor-Like Growth Factor Increases Peripheral Glucose Disposal and Insulin Sensitivity

Abstract: Physical exercise ameliorates metabolic disorders such as type 2 diabetes mellitus and obesity, but the molecular basis of these effects remains elusive. In the present study, we found that exercise up-regulates heparin-binding epidermal growth factor-like growth factor (HB-EGF) in skeletal muscle. To address the metabolic consequences of such gain of HB-EGF function, we generated mice that overexpress this protein specifically in muscle. The transgenic animals exhibited a higher respiratory quotient than did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…However, other ERBB ligands could be involved in regulating ERBB activation in db/db mice. Indeed, other ligands, which have been involved in metabolic disorders, can modulate ERBB phosphorylation state 25 , such as NRG4 26, 27 , betacellulin 28, 29 , epiregulin 30 or proheparin-binding EGF-like growth factor (HB-EGF) 31, 32 . As many biological processes can be regulated through ERBB, the functional consequences of the modified ERBB abundance and phosphorylation state in diabetes are difficult to predict.…”
Section: Discussionmentioning
confidence: 99%
“…However, other ERBB ligands could be involved in regulating ERBB activation in db/db mice. Indeed, other ligands, which have been involved in metabolic disorders, can modulate ERBB phosphorylation state 25 , such as NRG4 26, 27 , betacellulin 28, 29 , epiregulin 30 or proheparin-binding EGF-like growth factor (HB-EGF) 31, 32 . As many biological processes can be regulated through ERBB, the functional consequences of the modified ERBB abundance and phosphorylation state in diabetes are difficult to predict.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to VEGF, the ability of skeletal muscle to function as a trophic factor-producing organ has increasingly been recognized (40,62). Several cytokines and growth factors, including EGF, FGF, HGF, IGF, and NGF have all been shown to be produced by skeletal myocytes (3,15,22,56,60). However, the capacity for trophic factor production can be aberrantly downregulated, as seen in human dilated cardiomyopathy for VEGF (1) and human heart failure for NGF (24).…”
Section: Discussionmentioning
confidence: 99%
“…3). It has been reported that insulin stimulation increased the phosphorylations of Akt at Ser473/Thr308 and Foxo1 at Thr24 and reduced the mRNA content of PDK4 in the gastrocnemius muscle [38]. It is noteworthy that the elevation of Foxo1 phosphorylation was accompanied by increased whole-body glucose uptake and attenuated hepatic glucose production [38].…”
Section: Foxo1 As a Negative Regulator Of Glucose Utilization In The mentioning
confidence: 99%
“…It has been reported that insulin stimulation increased the phosphorylations of Akt at Ser473/Thr308 and Foxo1 at Thr24 and reduced the mRNA content of PDK4 in the gastrocnemius muscle [38]. It is noteworthy that the elevation of Foxo1 phosphorylation was accompanied by increased whole-body glucose uptake and attenuated hepatic glucose production [38]. In contrast, experimental simulation of insulin-resistant states by infusion of intralipid/lactate and insulin in rats reduced the protein contents of phosphorylated Akt Ser307 and Foxo1 Ser319 and induced transcriptional activation of PDK4 in the gastrocnemius muscle [39].…”
Section: Foxo1 As a Negative Regulator Of Glucose Utilization In The mentioning
confidence: 99%
See 1 more Smart Citation